ASSESSMENT STUDIES RELIGIOUS EDUCATIONAL EDUCATION MADRASAH DINIYAH TAKMILIYAH (MDT) IN HONG KONG - Iyoh Mastiyah (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2018)
EnglishThis study describes the pilot project of religious education in the form of Madrasah Diniyah Takmiliyah (MDT) in Hong Kong. The findings show that Islamic Religious Education in HK has developed both in the form of organizations and Islamic teaching circles (Majelis Taklim). However their roles are considered limited, for they only provide religious education for adults and for children. This situation is due to the lack of competent teachers of Islamic subjects. Islamic Religious Education for children is available at the Consulate General office although the supporting factors are still limited. To boost further development, a stakeholder committee of the madrasah has been formed by taking into account all potentials and opportunities. IndonesiaStudi ini mendeskripsikan rintisan pendidikan keagamaan Madrasah Diniyah Takmiliyah (MDT) di Hong Kong. Temuan penelitian menunjukan bahwa perkembangan Pendidikan Keagamaan di HK cukup menggembirakan terbukti banyaknya lembaga Pendidikan Keagamaan baik dalam bentuk organisasi maupun Majelis Taklim yang kegiatannya cukup semarak. Namun peranannya dalam pendidikan keagamaan Islam masih terbatas, baik untuk orang dewasa maupun untuk anak-anak. Karena kurangnya tenaga ustadz yang memiliki kompetensi di bidang agama. Walaupun Pendidikan Keagamaan Islam bagi anak-anak telah tersedia di KJRI, namun kondisinya masih terbatas. Oleh karena itu berdasarkan peluang dan potensi yang tersedia, telah disepakati adanya rintisan Madrasah Diniyah Takmiliyah yang diikuti komitmen (agreement) dengan terbentuknya stackeholder atau tim penyelenggara rintisan Madrasah Diniyah Takmiliyah di Hong Kong.